Design for a Biomass-Based Hydrogen Plant for an Existing Petroleum Refinery - AlHussein Mohamed Hazem AlTaranissi, AlHussein Mohamed Hazem (Universiti Teknologi Petronas, 2009)
Hydrogen is used in petroleum refineries in hydrotreating and hydrocracking processes. At the same time, hydrogen is a by-product of the petroleum refining processes. However, this hydrogen is not sufficient to meet the refinery’s total requirement. A hydrogen plant is often built near to the petroleum refinery to supply it with its total needs of hydrogen. In the hydrogen plant, hydrogen can be industrially produced by several processes; Electrolysis, gasification of coal and natural gas reforming. However, there are some issues associated with the hydrogen production processes stated above; high cost of electricity when using electrolysis, the depletion of source of fossil fuel, fluctuation of prices of natural gas and the greenhouse gas emissions from fossil fuel. Therefore, in this study, we are proposing to design a hydrogen plant that uses biomass as its feedstock aiding the petroleum refineries with their needs of hydrogen and solving the issues states above. Rice husk and rice straw are types of biomass that can be used to produce hydrogen in the hydrogen plant. In this study, gasification of biomass was applied for the rice husk and rice straw to produce hydrogen. The reaction kinetics were first gathered, then the general equation for gasification of biomass has been solved using MATLAB and finally a flowsheet has been developed and simulated using iCON simulator which is a PETRONAS owned simulation software.